The Intensification of surveillance : crime, terrorism and warfare in the information age - Ball, Kirstie; Webster, Frank (London ; Sterling, VA : Pluto Press, 2003)
Shocking expose of surveillance methods. Shows how we can combat crime without eroding civil liberties.
The intensification of surveillance / Kirstie Ball and Frank Webster -- Surveillance after September 11th / David Lyon -- Data-mining and surveillance in the post 9-11 environment / Oscar Gandy -- Joined-up surveillance? / Charles Raab -- 'They don't even know we're there': the electronic monitoring of offenders in England and Wales / Mike Nellis -- Information warfare, surveillance and human rights / Frank Webster -- Mapping out cybercrimes in a cyberspatial surveillant assemblage / David Wall.
Includes bibliographical references (pages 154-168) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Privacy, Right of; Electronic surveillance -- Social aspects; Social control; War on Terrorism, 2001-2009.; Operation Enduring Freedom, 2001-2014.; Social Control, Formal; Droit à la vie privée.; Surveillance électronique -- Aspect social; Contrôle social; Opération Liberté immuable, 2001-2014.; Guerre contre le terrorisme, 2001-2009.; LAW -- Forensic Science; POLITICAL SCIENCE -- Human Rights; Electronic surveillance -- Social aspects; Privacy, Right of; Social control; 2001-2009